Lehman Syndrome: A New Syndrome for Pierre Robin Sequence. (May 2015) - Correia-Sá, Inês; Horta, Ricardo; Neto, Tiago; Amarante, José; Marques, Marisa
Lehman syndrome, or lateral meningocele syndrome, is characterized by facial dysmorphism, multiple lateral meningoceles, and skeletal abnormalities. Only nine cases have been described. We present a case of a 2-year-old boy presenting with micrognathia, glossoptosis, and hypertelorism as well as associated severe obstructive sleep apnea. He was submitted to bilateral mandibular distraction with external nonresorbable devices to correct Pierre Robin sequence (PRS). Later, multiple lateral meningoceles were identified, and a diagnosis of Lehman syndrome was made. Lehman syndrome must be considered in syndromic infants with PRS. Distraction osteogenesis is a safe procedure that is effective as a first choice in the treatment of patients with Lehman syndrome presenting with micrognathia.